Zastosowanie analizy kanonicznej na polskim rynku energii elektrycznej - Ganczarek, Alicja (An Application of the Canonical Analysis on Polish Energy Market, 2005)
In this paper we presented an application of the canonical analysis on the day-ahead market of the energy market CIRE. We have two sets of prices and volumes of electric energy were noted on CIRЕ from July 2002 to June 2004. The aim of this paper was the classification the energy markets and the classification the prices and volumes of electric energy during a day. In the next step we use this classification to describe dependence between these sets. We described this dependence with regression equation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 162-170